Role of external and internal perturbations on ferromagnetic phase transitions in manganites: existence of tricritical points. (28th June 2018) - Mukherjee, Prabir K; Sarkar, Prosenjit; Chattopadhyay, Amit K
Abstract: A phenomenological mean-field theory is presented to describe the role of external magnetic field, pressure and chemical substitution on the nature of ferromagnetic (FM) to paramagnetic (PM) phase transition in manganites. The application of external field (or pressure) shifts the transition, leading to a field (or pressure) dependent phase boundary along which a tricritical point is shown to exist where a first-order FM-PM transition becomes second-order. We show that the effect of chemical substitution on the FM transition is analogous to that of external perturbations (magnetic field and pressure); this includes the existence of a tricritical point at which the order of transition changes. Our theoretical predictions satisfactorily explain the nature of FM-PM transition, observed in several systems. The modeling hypothesis has been critically verified from our experimental data from a wide range of colossal magnetoresistive manganite single crystals like Sm0.52 Sr0.48 MnO3 . The theoretical model prediction of a tricritical point has been validated in this experiment which provides a major ramification of the strength of the model proposed.